Does time heal fatigue, psychological, cognitive and disability problems in people who experience an out-of-hospital cardiac arrest? Results from the DANCAS survey study. (January 2023) - Joshi, Vicky L.; Tang, Lars Hermann; Mikkelsen, Tina Broby; Nielsen, Jørgen Feldbæk; Zinckernagel, Line; Borregaard, Britt; Agarwal, Sachin; Kjær Ersbøll, Annette; Yonis, Harman; Kragholm, Kristian; Hassager, Christian; Zwisler, Ann-Dorthe
Abstract: Aims: Out-of-hospital cardiac arrest (OHCA) survivors may suffer short-term fatigue, psychological, cognitive and disability problems, but we lack information on the proportion of survivors with these problems in the long-term. Hence, we investigated these problems in survivors 1–5 years post-OHCA and whether the results are different at different time points post-OHCA. Methods: All adults who survived an OHCA in Denmark from 2016 to 2019 were identified using the Danish Cardiac Arrest Registry and invited to participate in a survey between October 2020 and March 2021. The survey included the Modified Fatigue Impact Scale, Hospital Anxiety and Depression Scale, "Two simple questions" (everyday activities and mental recovery), and the 12-item World Health Organisation Disability Assessment Schedule 2.0. To investigate results at different time points, survivors were divided into four time-groups (12–24, 25–36, 37–48 and 49–56 months post-OHCA). Differences between time-groups were determined using the Kruskall-Wallis test for the mean scores and Chi-square test for the proportion of survivors with symptoms. Results: Total eligible survey population was 2116, of which 1258 survivors (60 %) responded. Overall, 29 % of survivors reported fatigue, 20 % anxiety, 15 % depression, and 27 % disability. When survivors were sub-divided by time since OHCA, no significant difference was found on either means scores or proportion between time groups (p = 0.28 to 0.88). Conclusion: Up to a third of survivors report fatigue, anxiety, depression, reduced mental function and disability 1–5 years after OHCA. This proportion is the same regardless of how much time has passed supporting early screening and tailored post-OHCA interventions to help survivors adapt to their new situation.